Determining Disclosure of Tax Avoidance - Richard Andrew; Yosef Pranata (CONTABILITA : Journal of Accounting and Finance, 2025)
The purpose of the study was to find out how profitability, capital intensity, company size, and are affected by tax avoidance. The sample for this study were 34 mining companies listed between 2018 and 2022 on the Indonesia Stock Exchange. The random effect Model (REM) was the selected test model, and the panel regression data were tested using the eviews 12 program. Profitability research results provide significant positive results against tax avoidance. The company size of the business significantly affects tax avoidance in a negative direction. Meanwhile, capital intensity has no effect on tax avoidance.